The theory of financial intermediation - Allen, Franklin; Santomero, Anthony M (Journal of Banking & Finance, 1997)
Traditional theories of intermediation are based on transaction costs and asymmetric information. They are designed to account for institutions which take deposits or issue insurance policies and channel funds to firms. However, in recent decades there have been significant changes. Although transaction costs and asymmetric information have declined, intermediation has increased. New markets for financial futures and options are mainly markets for intermediaries rather than individuals or firms. These changes are difficult to reconcile with the traditional theories. We discuss the role of intermediation in this new context stressing risk trading and participation costs.